2022
DOI: 10.3390/joitmc8010047
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Business Strategies in the Face of COVID-19: An Approach to Open Innovation of SMEs in the Sonora Region of Mexico

Abstract: The purpose of this study is to analyze and verify the effects of the business strategy (financial and market) and innovation management exerted on the economic indicators and business performances of SMEs in the south-central region of Sonora in Mexico. The effect of electronic commerce and the home office in the management of innovation and corporate performance is also analyzed. In addition, a multigroup analysis was carried out to check if there are significant differences between family and non-family bus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 140 publications
0
7
0
Order By: Relevance
“…The logical aftereffects of this observational concentrate likewise gave data to grow the information of strategic intuition (SI). Valdez-Juárez et al [23] analysed and verified the effects of the business strategy (financial and market) and innovation management exerted on the economic indicators and business performances of SMEs in the south-central region of Sonora in Mexico. The outcomes reported that the business technique (monetary and market) doesn't fundamentally affect the administration of advancement and the financial signs of SMEs.…”
Section: Literature Surveymentioning
confidence: 99%
“…The logical aftereffects of this observational concentrate likewise gave data to grow the information of strategic intuition (SI). Valdez-Juárez et al [23] analysed and verified the effects of the business strategy (financial and market) and innovation management exerted on the economic indicators and business performances of SMEs in the south-central region of Sonora in Mexico. The outcomes reported that the business technique (monetary and market) doesn't fundamentally affect the administration of advancement and the financial signs of SMEs.…”
Section: Literature Surveymentioning
confidence: 99%
“…Currently, innovation is the basis for business development. There is research on new models of open innovation for businesses [ 58 , 59 , 60 , 61 , 62 ], especially for digital companies [ 63 ], which are an achievable direction in Industry 4.0 [ 64 ]. Business models have also recently been a subject for research related to the pandemic; for example, they refer to the COVID-19 crisis [ 65 ], mobile market during COVID-19 [ 13 ], COVID-19 transformation of an urban public transport system [ 66 ], management after COVID-19 [ 67 ], and identification of digital transformation paths in the business model of SMEs during the COVID-19 pandemic [ 68 , 69 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Clearly, the Covid-19 pandemic will lead to new business strategies and "modus operandi" that will reshape the business landscape post-crisis. New technologies will emerge generating new ways of interactions at the GtoG, BtoB, and BtoC segments of the economy (Chollisni, Dewi, Utama, & Anas, 2022;IBM, 2020;Valdez-Juarez & Ramos-Escobar, 2022).…”
Section: Introductionmentioning
confidence: 99%